Expanding the Curricular Space with Educational Robotics: A Creative Course on Road Safety - Ioannou, Andri; Socratous, Chrysanthos; Nikolaedou, Elena (My University, 2018)
While initiatives worldwide continue to place pressure on schools to improve STEM education, the already overcrowded curriculum often leaves little space for the integration of new courses or topics. Numerous benefits are reported in the literature about the use of educational robotics; yet, their integration in school contexts requires time that cannot be taken from other important courses. In the end, most educational robotics activities are done outside the curriculum such as in after-school programs and summer camps. The major contribution of this work is the presentation of a case of creative and non-intrusive integration of educational robotics to support the current school curricula. We present an example of expanding the curricular space, by integrating educational robotics in an existing course unit. In the absence of formal educational robotics curriculum and courses, the study presents an exemplar case of educational robotics integration in a creative and non-intrusive way. The lesson design and implementation are presented; the creative infusion can be realized and holds benefits for the students. Through educational robotics, students can practice new skills such as problem solving and teamwork, while they gain knowledge in the specific domain of the course unit.
Keywords: Bee-Bot; Educational robotics; Expanding the curricular space; K-12; Technology integration